2019
DOI: 10.1093/ejcts/ezz171
|View full text |Cite
|
Sign up to set email alerts
|

Familial spontaneous pneumothorax: importance of screening for Birt–Hogg–Dubé syndrome

Abstract: OBJECTIVES The goal of this study was to investigate the prevalence of Birt–Hogg–Dubé (BHD) syndrome in patients with familial spontaneous pneumothorax (FSP) and the clinical characteristics of pneumothorax related to BHD syndrome compared with those of primary spontaneous pneumothorax. METHODS A total of 37 families diagnosed with FSP from 2007 to 2017 were enrolled in this study. The FLCN gene, which is responsible for BHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
2
24
0
1
Order By: Relevance
“…1). Using the study criteria outlined above, 221 cases from 120 families with BHDS were included in the final analysis, which were reported in 20 papers (Table 1) [8][9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In 2008, the first 10 families with spontaneous pneumothorax and positive FLCN mutations in the Chinese population were described by a research team at Nanjing University [8].…”
Section: Demographic Datamentioning
confidence: 99%
“…1). Using the study criteria outlined above, 221 cases from 120 families with BHDS were included in the final analysis, which were reported in 20 papers (Table 1) [8][9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In 2008, the first 10 families with spontaneous pneumothorax and positive FLCN mutations in the Chinese population were described by a research team at Nanjing University [8].…”
Section: Demographic Datamentioning
confidence: 99%
“…In patients presenting with apparent primary spontaneous pneumothorax, a positive family history of pneumothorax was highly predictive of BHD diagnosis, with prevalence rates of 64-86% [125,126]. Indeed, BHD appears to be the single most common cause of familial pneumothorax [127]. One study suggested that, in patients presenting with apparent primary pneumothorax, HRCT screening for an underlying diffuse cystic lung disease such as BHD, LAM or PLCH is cost-effective and should be recommended [67].…”
Section: Diagnosis Of Bhdmentioning
confidence: 99%
“…BHDS-related pneumothorax seems to have a higher recurrence rate after conservative therapy (observation, chest drainage and chemical pleurodesis) compared to surgical management. Liu et al reported only 9% of patients had recurrence of pneumothorax after surgical treatment (pulmonary bullectomy and/or pleurodesis) while 52% of recurrence rate was observed after conservative treatment 24 . Gupta et al reported pleurodesis (chemical or surgical) to reduce the ipsilateral recurrence rate by half (33% versus 63%) 30 .…”
Section: Discussionmentioning
confidence: 99%